Disclosure of insurability risks in research and clinical consent forms. Issue 1 (2nd January 2016) - Salman, Shahad; Ngueng Feze, Ida; Joly, Yann
ABSTRACT: Genetic testing results and research findings raise concerns about access to genetic information by insurers. Recently, the Canadian Life and Health Insurance Association reaffirmed its prerogative to request, for underwriting purposes, the disclosure of clinical and research genetic test results if the participant/patient or his physician has knowledge of the results. Studies have shown that access to genetic information to determine insurability can, in limited instances, lead to actual, or fear of, genetic discrimination, result in individuals refusing to undergo testing or declining participation in genomic research, and being asked to pay higher premiums or denied access to certain types of insurance. Obtaining informed consent for genetic testing and genomic research is crucial and should take into account the potential need to disclose possible insurability risks to patients and participants. Our study analyzed clinical and research consent forms, templates and guidelines from Quebec to investigate two questions: (1) whether consent forms include clauses providing information on potential insurability risks and (2) when such potential risks are included, what information is provided and how it is formulated. Our findings show that current information on insurability risks in Quebec's forms/guidelines lack coherence, potentially resulting in patients/participants receiving inconsistent information.